PENGARUH FLOURIDE TERHADAP SIFAT MEKANIK GIGI TIRUAN BERBAHAN DASAR LIMBAH CANGKANG TELUR AYAM - Baiq R. S. Yusuf; Siti Alaa; Dian W. Kurniawidi; Susi Rahayu (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2019)
The fabrication of dentures from the eggshell has been done using the precipitation method. FTIR and AAS tests were carried out to determine the functional groups and calcium oxide content in egg shells. From the AAS results, the CaO value is 58.33% which is much greater than the minimum standard CaO in dentures. Mechanical tests were carried out on dentures treatment with immersion into distilled water and the results were compared if immersion using fluoride toothpaste. It was found that immersion with fluoride toothpaste can increase the elasticity of dentures by more than 100%.